Fishes of the Northern Mid-Atlantic Ridge collected during the MAR-ECO cruise in June-July 2004 : An Annotated Checklist - Porteiro, Filipe M. A. (2017)
Records of the fishes from the northern Mid-Atlantic Ridge (MAR) (41⁰N - 60⁰N) sampled during two research cruises conducted in summer 2004 on the R/V G.O. Sars and M/S Loran are presented. The cruises were major sampling efforts carried out for the MAR-ECO project, i.e. the Census of Marine Life field project entitled “Patterns and Processes of the Ecosystems of the Northern Mid-Atlantic”. The investigation included sampling with several midwater nets, bottom trawl and longlines from surface waters to about 4000 m. The list comprises around 300 species of fishes from 82 families. Many records were new to the northern mid- Atlantic area, and the list also comprises three recently described species and some additional specimens to date only identified to genus.